Comprehensive Medical Approach to a Hikikomori (social withdrawal) Patient with Severe Dental Phobia - Beppu, Satoshi; Satoh, Tomokazu; Yoshida, Kazuichi; Yasuda, Michiko; Kagawa, Keita; Imaizumi, Uno (Comprehensive Medicine, 2019)
Hikikomori, or social withdrawal is defined as a phenomenon exhibited by a person who avoids social contact as a result of various factors and stays at home for more than six months. It is critical to adopt a comprehensive medical approach when a patient is socially withdrawn and has severe dental phobia and a deep mistrust of dental treatment. This particular case involved a male patient in his 20s. He was undergoing psychiatric treatment for panic disorder, depression and social withdrawal which he had developed several years previously. Although he had toothache, he had a strong fear of dental treatment because of his past dental experience and suffered from posttraumatic stress disorder(PTSD). As his toothache became unbearable, he decided to visit our clinic where patients can receive dental treatment under general anesthesia. Since he was unable to go outside, we first made a house call. However, as we treated the patient, he experienced strong nausea as if he had refused treatment and could not open his mouth. After a comprehensive physical, psychological, social and existential evaluation of the patient, we determined treatment methods. While asking his family to persuade the patient to visit our dental clinic, we focused our effort on the creation of rapport with him. As a result, the patient gradually became able to go outside and even come to see us for a pre-anesthesia testing. The patient finally received dental treatment under general anesthesia, which freed him from his toothache. Currently, we are giving him preventive dentistry so that similar problems will not occur again. We learnt from this case that ordinary treatment methods were not enough to treat a hikikomori patient with severe dental phobia, and that the use of general anesthesia should be necessarily considered as an option. Furthermore, it was deemed necessary to continuously remind a patient of the importance of preventative oral care that could prevent recurrence of dental problems.